Thieno[3, 2‐b]thiophene Flanked Isoindigo Polymers for High Performance Ambipolar OFET Applications. (10th September 2014) - Meager, Iain; Nikolka, Mark; Schroeder, Bob C.; Nielsen, Christian B.; Planells, Miquel; Bronstein, Hugo; Rumer, Joseph W.; James, David Ian; Ashraf, Raja Shahid; Sadhanala, Aditya; Hayoz, Pascal; Flores, Jean‐Charles; et al.
<x xml:space="preserve">Abstract</x> The synthesis of a new thieno[3, 2‐b]thiophene isoindigo (iITT) based monomer unit, and its subsequent incorporation into a series of alternating copolymers is reported. Copolymerisation with benzothiadiazole, bithiophene and thiophene comonomer units by palladium catalysed cross coupling gives three new narrow band gap semiconducting polymers for OFET applications. Extending the fused nature of the isoindigo core serves to further enhance molecular orbital overlap along the polymer backbones and facilitate good charge transport characteristics thus demonstrating the potential of extending the fused ring system that is attached to the isoindigo core. When used as the semiconducting channel in top‐gate/bottom‐contact OFET devices, good ambipolar properties are observed, with hole and electron mobilities up to 0.4 cm2/Vs and 0.7 cm2/Vs respectively. The three new polymers show good stability, with high temperature annealing showing an increase in the crystallinity of the polymers which corresponds directly to charge carrier mobility improvement as shown by X‐ray diffraction, atomic force microscopy and photothermal deflection spectroscopy.